A LITERARY REVIEW OF MEDICINAL USE OF AMRITMANJARI RASA IN TAMAKA SHWASA (BRONCHIAL ASTHMA) - Aneeta Kumari; Ajay Kumar Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study is designed to determine the specific beneficial effects of Amritmanjari Rasa by employing a combination of clinical observations, patient-reported outcomes, and comparative analyses against standardized asthma treatments. Traditional Ayurvedic texts suggest that the formulation possesses significant anti-inflammatory and bronchodilatory properties, yet empirical studies validating these claims in the context of asthma remain sparse. This lack of rigorous scientific inquiry presents a critical research problem that necessitates thorough exploration. Understanding the bioactive components of Amritmanjari Rasa and their mechanisms of action in the respiratory system is imperative for establishing the formulations therapeutic efficacy. The indepth review indicated marked enhancements in peak expiratory flow rates and reduced reliance on rescue inhalers, thereby positioning Amritmanjari Rasa as a potent adjunctive therapy in the management of bronchial asthma. The originality of this study lies not only in its focus on an under-researched Ayurvedic formulation but also in its methodological rigor, combining traditional knowledge with contemporary clinical evaluation frameworks. The implications of these findings extend beyond mere academic interest; they pose significant potential for re-evaluating treatment protocols for bronchial asthma, particularly in populations where conventional treatments may not yield satisfactory outcomes or where patients encounter adverse reactions to standard medications. The integration of herbal formulations like Amritmanjari Rasa into current therapeutic regimens can enhance patient adherence to treatment plans, ultimately fostering a holistic approach to respiratory health.